Navigating the landscape of Postpartum Depression: a comprehensive review - Panuciak, Kinga; Pawlik, Paweł; Trąbka, Natalia; Demidowicz, Gabriela; Lasek, Patryk; Lasota, Nina; Smerdzyński, Maciej; Ściurka, Kinga; Kowalczyk, Klaudia; Kozicka, Karolina (Journal of Education, Health and Sport, 2024)
Introduction and purpose: The joyous occasion of childbirth is often overshadowed by the prevalence of postpartum depression (PPD), a complex mental health condition affecting mothers globally. This paper reviews the current state of knowledge on PPD, exploring its frequency, risk factors, pathogenesis, symptoms, and impact on maternal and child health. Description of the State of Knowledge: Recent studies indicate an alarming increase in PPD rates, with notable racial and socioeconomic disparities. Symptoms of PPD, ranging from mild to severe include mood disturbances, cognitive impairments, and self-harm ideation. The repercussions extend beyond the postpartum period, affecting long-term child development, breastfeeding practices, and the mother-infant bond. Advancements in screening tools, particularly the Edinburgh Postnatal Depression Scale (EPDS), have facilitated early detection. However, creating an environment conducive to open communication about mental health remains a significant challenge. Interventions for PPD include psychotherapeutic approaches, pharmacological interventions, and complementary therapies. Brexanolone, the first FDA-approved drug for PPD, represents a significant breakthrough. Community-based and peer support programs, alongside a multidisciplinary approach involving healthcare professionals and support networks, have shown promise in alleviating PPD symptoms. Summary: In conclusion, PPD remains a substantial public health concern. Increased awareness of its multifaceted nature has led to improved screening, diagnosis, and intervention strategies. Ongoing dialogue, supportive environments, and refined treatments are essential for enhancing the well-being of both mothers and their infants in the postpartum period.